2001
DOI: 10.1139/l01-068
|View full text |Cite
|
Sign up to set email alerts
|

Structural performance of sliplined watermain

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Additionally, based on the trend of load changes after cracking, the bearing capacity of the pipe sections with a pinned interface no longer increased during the continued loading process due to serious interfacial peeling and remained at a certain level, while the bearing capacity of the pinned and naturally bonded interfacial pipe sections underwent a certain increase after the pipe sections cracked. This illustrates that as the interfacial bonding increased, the longer the pipe in the laminated structure, the more effectively the liner layer functions, resulting in an increased bearing capacity of the after the repair was carried out [23,24].…”
Section: Comparison Of the Ultimate Load And Load Capacity Improvementmentioning
confidence: 99%
“…Additionally, based on the trend of load changes after cracking, the bearing capacity of the pipe sections with a pinned interface no longer increased during the continued loading process due to serious interfacial peeling and remained at a certain level, while the bearing capacity of the pinned and naturally bonded interfacial pipe sections underwent a certain increase after the pipe sections cracked. This illustrates that as the interfacial bonding increased, the longer the pipe in the laminated structure, the more effectively the liner layer functions, resulting in an increased bearing capacity of the after the repair was carried out [23,24].…”
Section: Comparison Of the Ultimate Load And Load Capacity Improvementmentioning
confidence: 99%
“…In 2013 investigation of the status of the channel was organized and a restoration plan was subsequently devised. A section of 875 meters was identified in need of immediate rehabilitation [13]. The damage included corrosion, leaks and infiltration, which was facilitated by the proximity of the River Main.…”
Section: Case Study: Relining Project In Würzburg Germanymentioning
confidence: 99%
“…A total of 401 non-circular profiles in lengths of 1 to 2.35 m and with a wall thickness of 25 mm were used in the rehabilitation of the old sewer [13].…”
Section: Case Study: Relining Project In Würzburg Germanymentioning
confidence: 99%
“…McAlpine believes that the mortar lining forms a composite structure with the original pipeline and it was found that the lining was mainly tensile and the bending stiffness of the pipeline increased after repair [ 16 ]. Zhao and Daigle think that the lining layer and the original pipe form a composite structure and that the interface is completely smooth [ 17 ]. The lining thickness also has a great influence on the pipeline performance.…”
Section: Introductionmentioning
confidence: 99%